10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Malaria has long been considered a rural disease. However, rapid urbanization, the expansion of urban malaria vectors, and the subsequent, ongoing surge in malaria cases across sub-Saharan Africa, including Ethiopia, underscore the need to address malaria in urban contexts. This study therefore aims to explore the acceptability of insecticide-treated bed nets (ITNs) in an urban setting using the theoretical framework of acceptability. Eight Focus Group Discussions (FGDs), comprising a total of 48 participants, were conducted in the four Kebeles of Batu town, East Shoa, Oromia, Ethiopia. A semi-structured interview guide, developed based on the constructs of the Theoretical Framework of Acceptability (TFA), was used to facilitate the discussions. Data were analyzed using content analysis with a deductive approach, focusing on the seven components of the TFA. All data were managed with Atlas. ti software, version 9. Participants demonstrated a strong understanding of ITNs, expressing positive attitudes and noting a reduction in malaria cases following their introduction. However, concerns regarding the ethicality of ITNs emerged, particularly in relation to sexual assault and the discomfort experienced by pregnant women due to chemical exposure, which was perceived as violating the principle of non-maleficence. Participants also voiced dissatisfaction with the short height of currently available ITNs and expressed mixed feelings about their shapes; women preferred circular shaped nets, while men favored squared ones. In addition, they reported burdens such as adverse skin and respiratory reactions. Female participants, in particular, emphasized the increased household chores associated with handling the ITNs as a part of their morning routine. In conclusion, ITNs can be considered an appropriate intervention in controlling urban malaria. However, practical challenges must be addressed to improve their acceptance and usability.